Development and field evaluation in African and Asian countries of an hepatitis B virus PCR on open polyvalent platforms to determine treatment eligibility: results from the "Agence Nationale de Recherche sur le Sida et les hépatites" 12327 study - Kania, Dramane; Nouhin, Janin; Bolloré, Karine; Njouom, Richard; Toni, Thomas d'Aquin; Maiga, Almoustapha Issiaka; Toure-Kane, Coumba; Ngo-Giang-Huong, Nicole; Dagnra, Anoumou; Chuong Le, Duy Hoang; Lunel-Fabiani, Françoise; Castera-Guy, Joany; et al. (Clinical microbiology and infection, 2024)
Widespread testing and treatment are essential to eliminate hepatitis B virus (HBV) infection as a public health concern. However, in resource-limited countries, access to HBV PCR is limited. In this study, we developed a quantitative HBV PCR assay on open molecular platforms and evaluate its performance in diagnosing clinically significant HBV DNA thresholds as defined by the WHO (2000 IU/mL, 20 000 IU/mL, and 200 000 IU/mL). We implemented our HBV PCR test in seven African and Asian countries and France, using either an in-house laboratory method or a European conformity for in vitro diagnostic (CE-IVD) marked version of the PCR (Generic HBV Charge Virale, Biocentric). Results were compared with reference tests (Roche Cobas AmpliPrep/Cobas TaqMan and Abbott RealTime on Abbott m2000). There was a good agreement between the HBV DNA results of 1015 samples tested by the PCR on open polyvalent platforms and the results from reference tests (mean difference (bias ± standard deviation [SD]): -0.3 ± 0.7 log IU/mL and -0.2 ± 0.9 log IU/mL when compared with Roche and Abbott tests, respectively). Kappa-Cohen agreements between the HBV PCR on open polyvalent platforms and the Roche/Abbott assays appeared almost perfect for HBV DNA levels ranged from >20 000 to 200 000 IU/mL and >200 000 IU/mL, substantial and moderate for HBV DNA levels ranged from 2000 to 20 000 IU/mL when compared with Abbott and Roche, respectively. The assay's performance was consistent across genotypes A, B, C, D, and E. This field evaluation showed that our HBV PCR test is a valuable alternative to proprietary PCR systems. PCR assays on open platforms contribute to expanding clinical laboratory solutions for diagnosing individuals who meet the viral load criteria for antiviral therapy (>20 000 IU/mL) and mother-to-child prophylaxis (>200 000 IU/mL).